A re-classification of Old English nouns - Krygier, Marcin (My University, 2002)
The standard classification of Old English nominal inflections, employing the Proto-Germanic root structure, fails to reflect synchronic features of the system. This paper follows Kastovsky (1995) and Lass (1997) in rejecting the traditional model as incompatible with synchronic data, and postulates an alternative view on the categorization of Old English nouns. The new interpretation makes it possible to capture synchronic relationships within the Old English nominal paradigm, as well as predict developmental tendencies observable in the Middle English period.